Adaptation of Oil Palm Seedlings Inoculated with Arbuscular Mycorrhizal Fungi and Mycorrhizal Endosymbiotic Bacteria Bacillus subtilis B10 towards Biotic Stress of Pathogen Ganoderma boninense Pat - YENNI BAKHTIAR; SUDIRMAN YAHYA; WAHONO SUMARYONO; MEITY SURADJI SINAGA; SRI WILARSO BUDI (Indonesian Society for microbiology, 2012)
The effects of mycorrhizal endosymbiotic bacteria Bacillus subtilis B10 and composite of arbuscular mycorrhizal fungal spores in green house experiment were examined in order to evaluate their effectiveness and compatibility with oil palm seedlings in the presence of a fungal pathogen Ganoderma boninense, the most serious pathogen in oil palm (Elaeis guineensis Jacq) in Indonesia. A three factors experiment were conducted, with mycorrhizal inoculation (M0 and M1), bacterial B. subtilis B10 inoculation (B0 and B1), and G. boninense inoculation (G0 and G1) as the first, second, and third factors, respectively. The results showed that disease severity index, plant height, root dry-weight, and phosphorus uptake were affected by co-inoculation of mycorrhizal endosymbiotic bacteria B. subtilis B10 and composite of arbuscular mycorrhizal fungi. Co-inoculation of mycorrhizal endosymbiotic bacteria B. subtilis B10 and arbuscular mycorrhizal fungi did not only reduce the percentage of basal stem rot incidence, but also significantly increased plant height and phosphorus uptake by oil palm seedlings. Our results suggest that in oil palm seedlings mycorrhizal endosymbiotic bacteria B. subtilis B10 worked synergistically with arbuscular mycorrhizal fungi in increasing plant adaptation toward biotic stress of pathogen G. boninese and could be promising biocontrol agents.